Empowering Digital Pedagogy through ICT-Based Deep Learning for Numeracy and Computational Thinking in Elementary Schools - Yullys Helsa; Syafri Arlis; Melva Zainil; Hutkemri Zulnaidi; Bayu Rachman (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to strengthen elementary school teachers’ capacity to integrate ICT-based deep learning pedagogy in improving students’ numeracy and computational thinking (CT) literacy. The program involved 30 teachers within a local Teacher Learning Community and was implemented through participatory workshops and structured mentoring using a one-group pre-test–post-test design to examine program impact. The intervention focused on enhancing teachers’ competence in designing ICT-integrated lesson plans, learning activities, and assessments aligned with numeracy and CT indicators. Data were collected through teacher self-assessment, classroom observation, and students’ pre- and post-tests and analyzed descriptively to determine mean improvement and percentage gain. The results demonstrated a 24% increase in teachers’ ICT pedagogical competence, indicating strengthened instructional capacity. As a follow-up impact of improved teaching practice, students’ numeracy achievement increased by 24%, and computational thinking performance improved by 20%. These findings confirm that empowering teachers through ICT-integrated deep learning contributes to measurable improvements in instructional quality and supports the development of higher-order literacy skills. Overall, the program achieved its objective by reinforcing teacher capacity as the primary outcome, with positive learning gains emerging as a direct pedagogical impact within elementary classrooms.